Heritage BIM integration with mixed reality for building preventive maintenance - Fonnet, Adrien (2017)
Historical and cultural building conservation is nowadays limited to high value buildings and only receive financial support when serious issues arise. HeritageCARE project is willing to shift this mentality, towards "prevention is better than the cure". New technologies are able to support such motivation by improving building inspector work during their inspection routine. In that regard, mixed reality will be explored to offer easy and efficient interaction while remaining focused on the task at hand. Moreover, integration with historical building information model will ensure capture of localized data and easier exchange with stakeholders in case of renovation projects. This paper presents an architecture for a mixed reality application working towards this goal and a first prototype.